Almost perfect sequence pairs derived from Fermat quotient. Issue 10 (1st May 2019) - Luo, Lianfei; Ma, Wenping
Abstract : Sequence pairs with good correlation can be applied in many practical systems. In this Letter, the authors construct a class of p ‐ary sequence pairs of period 2 p 2 by interleaving two p ‐ary sequences derived from Fermat quotient, where p is an odd prime. In the authors' construction, sequence pairs have almost perfect correlation.